Pancreatic Endosonography: Clinical TNM Staging Compared to Histology - TL Tio (Canadian Journal of Gastroenterology)
Endosonography has been reported to be effective in the staging of gastrointestinal carcinoma. Pancreatic carcinoma is included in the new (1987) TNM classification. Resectability is abandoned in favour of depth of tumour invasion. In the author's preoperative study, endosonography was accurate for staging of tumour categories, and early stages of disease could be distinguished from advanced carcinomas. The presence or absence of regional lymph nodes can be detected. Tissue diagnosis by biopsy and endosonographyguidcd cytology is now possible. This imaging technique will become the standard procedure for the staging of pancreatic carcinoma.